2012
DOI: 10.1177/0363546512461740
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Agreement Among Surgeons on Anterior Cruciate Ligament Tunnel Placement

Abstract: This study demonstrates that surgeons do not currently uniformly agree on ideal single-bundle tunnel placement and that the TT technique may yield more poorly placed tunnels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 47 publications
1
35
0
Order By: Relevance
“…Achieving an anatomic footprint is considered critical to achieving tibiofemoral stability after an ACL reconstruction [1,3,10,11,30,38,43], yet there is currently little agreement on the ideal footprint placement of a singlebundle ACL reconstruction. McConkey et al [30] showed that when 12 surgeons reviewed the femoral and tibial tunnels in 72 cadaveric knees, there was poor agreement (\5%) on what was considered the ideal tunnel placement, although 88% of the femoral tunnels and 78% of the tibial tunnels were created within the study criteria [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Achieving an anatomic footprint is considered critical to achieving tibiofemoral stability after an ACL reconstruction [1,3,10,11,30,38,43], yet there is currently little agreement on the ideal footprint placement of a singlebundle ACL reconstruction. McConkey et al [30] showed that when 12 surgeons reviewed the femoral and tibial tunnels in 72 cadaveric knees, there was poor agreement (\5%) on what was considered the ideal tunnel placement, although 88% of the femoral tunnels and 78% of the tibial tunnels were created within the study criteria [4].…”
Section: Discussionmentioning
confidence: 99%
“…McConkey et al [30] showed that when 12 surgeons reviewed the femoral and tibial tunnels in 72 cadaveric knees, there was poor agreement (\5%) on what was considered the ideal tunnel placement, although 88% of the femoral tunnels and 78% of the tibial tunnels were created within the study criteria [4]. An anatomic femoral footprint with the TT technique can be achieved if the tibial tunnel is placed further posterior and medial [11,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the anatomic insertion areas allow for different anatomic tunnel positions and no tunnel position so far has been found to be superior to others, certain variability of tunnel positions can be assumed. McConkey et al [21] found in a cadaver study that there was a poor agreement among surgeons on tunnel positioning. In this study, tunnel positions of 12 surgeons completed femoral and tibial tunnel positioning on 72 cadaver knees, which were then evaluated by three independent reviewers on 3D-CT scan analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey showed a clear change in surgical technique with 63% of North American surgeons and 81% of surgeons worldwide preferring drilling through an anteromedial portal. 6 These approaches have been evaluated with cadaveric models, with McConkey and colleagues 11 finding femoral tunnels were ideal 86% of time using 2-incision technique, 66% of time using the anteromedial portal, and only 51% of the time with transtibial technique. Similar findings were shown by Gadikota and colleagues, 9 with significantly more of the femoral tunnel within the ACL footprint for anteromedial portal (86%) and outside-in (89%) techniques compared with the transtibial technique (73%).…”
mentioning
confidence: 99%